Pendampingan Kelompok UMKM Keripik Tradisional dalam Upaya Peningkatan Daya Saing Produk Usaha Lokal - Indrioko, Erwin; Umatin, Choiru; Fauziyah Laili, Ummiy; Nasichin Al Muiz, Mochamad (IKIP PGRI Bojonegoro, 2025)
Sukosewu Village has great economic potential in the Micro, Small and Medium Enterprises (MSMEs) sector, one of which is a group of traditional chips artisans who produce a variety of chips from local raw materials, such as Lompong, Eggplant, Bitter Gourd, Taro, Ontong (Banana heart), Gadung, Cassava, Yam, Eel, Spinach, Kenikir, Mushroom, Green Bean and Gambas and others. However, traditional chip MSMEs in the village face obstacles in developing their businesses such as limited knowledge and skills of group members in business management, product marketing, and attractive and hygienic packaging. This condition makes local chip products still unable to compete with similar products from other regions. This community service aims to provide assistance in the form of product packaging training and e-commerce socialization to traditional chip MSME groups in improving the competitiveness of their local products using the Asset Based Community Development (ABCD) approach. The ABCD method was chosen because it focuses on the potential and strengths that the community already has to be developed, not on the shortcomings that need to be corrected. The mentoring program was implemented through several stages: 1) community asset mapping, 2) group capacity building, 3) marketing strategy development, and 4) ongoing evaluation. The results of the service showed a significant improvement in several aspects: more standardized production capabilities, more attractive product packaging, and expansion of marketing networks, and increased sales turnover. The MSME players also showed increased confidence in managing and developing their businesses. This program proves that an asset-based approach is effective in empowering MSME communities to optimize their potential to increase the competitiveness of local products in the wider market..